Новый для науки представитель рода Halicyclops (Crustacea, Copepoda) из Днепровско-Бугского лимана - Монченко, В.И. (Вестник зоологии, 1974)
The new species Halicyclops longispinosus sp. n. is very remarkable for the presence of the strong hook on a distal joint of the second antenna, very elongated spines on the Ps, original form of the spines of endopod P1-P3, exopod P1, for the ratio (long to wide) of distal joint of endopod P, and for another taxonomic characters